Investments - Fairweather, W. L. B.; Fairbairn, Ian. (London : The English University Press, 1960)
The book deals with the process of judging an investment for income, risk, and resale value.
Includes bibliographical references and index.
ucj 15/01/2019
Loans
Keywords: Investments; Securities; Capital market; Portfolio management